2018
DOI: 10.21037/jtd.2018.03.143
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with the prognosis and long-term survival of patients with metastatic lung adenocarcinoma: a retrospective analysis

Abstract: Background: Outcome of patients with advanced non-small cell lung cancer (NSCLC) treated with platinum-based doublet chemotherapy is usually poor, with overall survival ranges from 8-13 months.However, the overall survival is improved to 21-28 months in the era of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI). This study aimed to explore the prognostic factors to predict longterm survival in the era of EGFR TKI. Methods: A total 1,030 patients were studied who had been diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
(47 reference statements)
1
17
0
Order By: Relevance
“…38 Similarly, Huang et al reported that EGFR-TKI treatment duration of more than one year plays an important role in long-term survival. 39 Our study has several limitations. First, the sample size was relatively small.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…38 Similarly, Huang et al reported that EGFR-TKI treatment duration of more than one year plays an important role in long-term survival. 39 Our study has several limitations. First, the sample size was relatively small.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Huang et al . reported that EGFR‐TKI treatment duration of more than one year plays an important role in long‐term survival …”
Section: Discussionmentioning
confidence: 99%
“…The results of our retrospective study did not provide a definitive answer to the question whether erlotinib increases LTS in patients with EGFR-mutated MAL. Recently the results of a large retrospective Chinese study suggested that an age younger than 60, absence of extrathoracic spread and EGFR TKI treatment duration of more than one year may play an important role in survival beyond five years (18).…”
Section: Discussionmentioning
confidence: 99%
“…25 Gains in survival due to improved systemic therapy (with the introduction of targeted agents and immune checkpoint inhibitors [ICIs]) have further inspired research into the oligometastatic paradigm, with the hypothesis that local therapy has greater benefit with improved control of micrometastatic disease. [26][27][28][29] Improvements in systemic therapy have also led to another novel application for ablative therapies: to eradicate areas of oligoprogression. Despite high initial response rates to targeted therapy with tyrosine kinase inhibitors (TKIs) and ICIs, acquired resistance remains a challenge, with a median PFS of approximately 10 months in patients treated with TKIs or pembrolizumab as first-line therapy.…”
Section: Introductionmentioning
confidence: 99%